PERATURAN HUKUM NEGARA DAN KEBIJAKAN NASIONAL YANG MENGATUR SISTEM SERTIFIKASI DAN TATA KELOLA PERKEBUNAN KELAPA SAWIT BERKELANJUTAN, TERMASUK PERAN PEMERINTAH DAN TANGGUNG JAWAB SOSIAL PERUSAHAAN DALAM MEWUJUDKAN KEBERLANJUTAN LINGKUNGAN DAN SOSIAL - Gunawan Widjaja (JOURNAL OF LAW AND NATION, 2025)
This study analyses Indonesian national laws and policies governing the certification system and sustainable palm oil plantation management, focusing on two main topics: the ISPO-based legal system through Law No. 39/2014 on Plantations and Minister of Agriculture Regulation No. 38/2020, as well as the role of the government as a regulator-supervisor and corporate social responsibility (CSR) in accordance with Law No. 40/2007. Using a normative legal literature review method, the study found that the national legal framework has succeeded in integrating the principles of economic, social and environmental sustainability, but its implementation is hampered by overlapping regulations, weak inter-agency coordination, and a formalistic approach to CSR. Synergy between the government, companies and the community is needed to bridge the gap between legal norms and field practices in order to realise an inclusive and environmentally friendly palm oil industry in line with the SDGs.